What do people do at work? A profile of U.S. jobs from the survey of workplace Skills, Technology, and Management Practices (STAMP) - Michael J. Handel (Journal for Labour Market Research, 2016)
This paper describes the survey of Skills, Technology, and Management Practices (STAMP), which emphasizes the use of behaviourally specific questions in order to improve the quality of job measures. Such measures yield better understanding of the absolute levels of job demands compared to items or scales with arbitrary units that lack definite meaning outside the framework of a particular survey. STAMP measures reveal most workers use relatively simple levels of math on their jobs, but there is a bifurcation of jobs in terms of the complexity of reading and especially writing that is required. Aside from managerial and professional occupations, the absolute level of academic skills required on most jobs does not appear to be very high. Likewise, computer use is widespread but most people use computers for fairly mundane office duties rather than more complex tasks; few workers use any kind of automated production equipment on their jobs. Well-developed employee involvement practices, such as self-directed teams, cover about one-fifth to one-quarter of the workforce. Very few workers report being affected by outsourcing and the numbers affected by technological displacement are almost imperceptible.
Keywords: 330; Arbeitsanforderungen; Arbeitssituation; Tätigkeitsmerkmale; EDV-Anwendung; Qualifikation; Fertigkeiten; Mathematik; Fachkenntnisse; Arbeitsorganisation; Arbeitswissenschaft; USA